Layered Double Hydroxide Hollowcages with Adjustable Layer Spacing for High Performance Hybrid Supercapacitor. Issue 49 (27th October 2021) - Ma, Jiamin; Xia, Jiale; Liang, Zhong; Chen, Xiaoyun; Du, Yaping; Yan, Chun‐Hua
Abstract: Layered double hydroxides (LDHs) have been considered as promising electrodes for supercapacitors due to their adjustable composition, designable function and superior high theoretic capacity. However, their experimental specific capacity is significantly lower than the theoretical value due to their small interlayer spacing. Therefore, obtaining large interlayer spacing through the intercalation of large‐sized anions is an important means to improve capacity performance. Herein, a metal organic framework derived cobalt‐nickel layered double hydroxide hollowcage intercalated with different concentrations of 1, 4‐benzenedicarboxylic acid (H2 BDC) through in‐situ cationic etching and organic ligand intercalation method is designed and fabricated. The superior specific capacity and excellent rate performance are benefit from the large specific surface area of the hollow structure and increasing interlayer spacing of LDH after H2 BDC intercalation. The sample with the largest layer spacing displays a maximum specific capacity of 229 mA h g −1 at 1 A g −1 . In addition, the hybrid supercapacitor assembled from the sample with the largest layer spacing and active carbon electrode has a maximum specific capacity of 158 mA h g −1 at 1 A g −1 ; the energy density is as high as 126.4 W h kg −1 at 800 W kg −1 and good cycle stability. Abstract : CoNi‐BDC hollowcage is obtained by intercalating H2 BDC ligand into the CoNi‐LDH nanocage through in‐situ cationic etching and organic ligand intercalation methods for the first time. The structure design and engineering strategies of molecular layer spacing regulation endow larger specific surface areas and increase the interlayer spacing of CoNi‐LDH, thereby evidently boosting their electrochemical performance.